Preserving History for the Next Generation: A Study on the History of Trisula in Indonesia - Cornellya, Safira; Nikmah, Farika (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to create a documentation design of the historical event of the 1968 Trisula Operation to preserve the historical information contained in the relics of the event. The Trisula Operation was a military operation conducted by the Indonesian Army in Bakung Village, South Blitar, to suppress the remnants of the PKI rebellion. This event holds significant historical value; however, the relics that serve as sources of historical information are now deteriorating due to environmental factors and a lack of proper preservation. This research uses an action research approach, focusing on documenting the Trisula Operation collections stored at the Brawijaya Museum in Malang. Data collection techniques include observation, interviews, documentation, and questionnaires with the museum management as research subjects. The data obtained are analyzed descriptively to evaluate the effectiveness of documentation as a form of historical preservation. The findings suggest that documentation in the form of archival source manuscripts can serve as a strategic solution to preserve historical information, support the educational function of the museum, and maintain the collective memory of the nation.